2021
DOI: 10.1186/s12933-021-01249-y
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and non-traditional risk factors for peripheral artery disease development/progression in patients with type 2 diabetes: the Rio de Janeiro type 2 diabetes cohort study

Abstract: Background The prognostic importance of non-traditional risk factors for peripheral artery disease (PAD) development/progression is scarcely studied in diabetes. We investigated if carotid intima-media thickness (CIMT) and carotid-femoral pulse wave velocity (cf-PWV) added prognostic information beyond traditional cardiovascular risk markers for PAD outcomes. Methods Ankle-brachial index (ABI) was measured at baseline and after a median of 91 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
1
13
0
6
Order By: Relevance
“…Multivariate logistic regression analysis indicated that LDL-C level was also an independent factor associated with PAD in diabetic patients (OR = 1.510, 95% CI = 1.152 to 1.980, p = 0.003). This fining is consistent with Cardoso et al's report that LDL-cholesterol was associated with PAD development/progression in patients with type 2 diabetes [12]. It is known that low levels of low-density lipoprotein cholesterol can effectively reduce the risk of vascular events [29].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Multivariate logistic regression analysis indicated that LDL-C level was also an independent factor associated with PAD in diabetic patients (OR = 1.510, 95% CI = 1.152 to 1.980, p = 0.003). This fining is consistent with Cardoso et al's report that LDL-cholesterol was associated with PAD development/progression in patients with type 2 diabetes [12]. It is known that low levels of low-density lipoprotein cholesterol can effectively reduce the risk of vascular events [29].…”
Section: Discussionsupporting
confidence: 89%
“…The independent factors associated with PAD in type 2 diabetic patients have been investigated. Cardoso et al have reported that increased carotid intima-media thickness and aortic stiffness were independent factors associated with PAD in type 2 diabetic patients [12]. Bertrand et al demonstrate that HDL-cholesterol, ApoA-I, total cholesterol/HDL-cholesterol ratio or non-HDL-cholesterol were independent factors associated with PAD in patients with type 2 diabetes [13].…”
mentioning
confidence: 99%
“…All participants gave written informed consent, and the local Ethics Committee had previously approved the study protocol. The characteristics of the participants of the whole Rio-T2D cohort, as well as of the individuals with NAFLD, its baseline procedures and diagnostic definitions, all have been detailed previously [ 21 26 ]. All participants with NAFLD had at least a previous abdominal ultrasound demonstrating any grade of liver steatosis and none of them had any other cause of liver steatosis except NAFLD.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcomes were the occurrence of any cardiovascular event (CVE) and all-cause mortality. Total CVEs included the following: fatal or non-fatal myocardial infarctions (MIs), sudden cardiac deaths, new-onset heart failure, death from progressive heart failure, any myocardial revascularization procedure, fatal or non-fatal strokes, any aortic or lower limb revascularization procedure, any amputation above the ankle, and deaths from aortic or peripheral arterial disease [ 24 26 ]. Primary outcomes were ascertained from medical records, death certificates and interviews with attending physicians and patient families, by a standard questionnaire reviewed by two independent observers [ 24 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation